Educational, psychological, and behavioral considerations in niche online communities - Venkatesh, Vivek; Wallin, Jason J. 1975-; Castro, Juan Carlos; Lewis, Jason Edward (Advances in social networking and online communities (ASNOC) book series, 2014)
"This book examines the presence of online communities centered around niche topics of interest and the impact of these virtual spaces on community members, offering perspectives from interdisciplinary fields such as sociology, psychology, and education"..